Redox Proteomics Analysis to Decipher the Neurobiology of Alzheimer-like Neurodegeneration: Overlaps in Down Syndrome and Alzheimer Disease Brain - Butterfield, D. Allan (Biochem J, 2014)
Accumulation of oxidative damage is a common feature of neurodegeneration that together with mitochondrial dysfunction point to the fact that reactive oxygen species are major contributors to loss of neuronal homeostasis and cell death. Among several targets of oxidative stress, free radical-mediated damage to proteins is particularly important in aging and age-related neurodegenerative diseases. In the majority of cases, oxidative stress mediated post-translational modifications cause non-reversible modifications of protein structure that consistently lead to impaired function. Redox proteomics methods are powerful tools to unravel the complexity of neurodegeneration, by identifying brain proteins with oxidative post-translational modifications that are detrimental for protein function. The present review discusses the current literature showing evidence of impaired pathways linked to oxidative stress possibly involved in the neurodegenerative process leading to the development of Alzheimer-like dementia. In particular, we focus attention on dysregulated pathways that underlie neurodegeneration in both aging adults with Down syndrome (DS) and AD. Since AD pathology is age-dependent in DS and shows similarities with AD, identification of common oxidized proteins by redox proteomics in both DS and AD can improve our understanding of the overlapping mechanisms that lead from normal aging to development of AD. The most relevant proteomics findings highlight that disturbance of protein homeostasis and energy production are central mechanisms of neurodegeneration and overlap in aging DS and AD. Protein oxidation impacts crucial intracellular functions and may be considered a “leitmotif” of degenerating neurons. Therapeutic strategies aimed at preventing/reducing multiple components of processes leading to accumulation of oxidative damage will be critical in future studies.